Legal Regulation of Producer Responsbility in Waste Management: An Extended Producer Responbility (EPR) Perspective in Indonesia - Farah Adriani; Imam Koeswahyono; Hanif Nur Widhiyanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2026)
Environmental issues, particularly waste management, have become increasingly complex in Indonesia due to rapid industrial development and the rising volume of waste, especially packaging waste. This condition highlights the need to strengthen legal regulation on producer responsibility in waste management. This study analyzes producer responsibility from the perspective of Extended Producer Responsibility (EPR) within the framework of a circular economy. The research uses a normative juridical method with statutory and conceptual approaches, focusing on legal instruments governing waste management in Indonesia. The findings show that EPR principles have been incorporated into several regulations, including Law Number 18 of 2008 on Waste Management, Government Regulation Number 81 of 2012, and Minister of Environment and Forestry Regulation Number 75 of 2019. However, EPR implementation remains limited due to regulatory weaknesses, such as the broad definition of producers, the absence of a clearly established Producer Responsibility Organization (PRO), and the lack of comprehensive economic instruments. Compared to international practices, particularly in the European Union and OECD, Indonesia’s EPR framework remains less developed. Therefore, clearer definitions, stronger institutional mechanisms, and operational frameworks are needed to ensure effective EPR implementation.